(3JYdjbI GdMGL CZG QVG GdgeOGfj Ydi ecGSH GdTjN GdCYXe GdCfUGQjs - (3GdgeOGfj, BZG, QVG Hf eMeO, J (B1322 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3cJGH GdHjY , bHd GdTQhY aj GdebUhO dGHO ef HjGf eYfi GdHjY hCfg gd ddTGQY Ch GdeJTQYI ajg GUWdGM NGU dCh gh eSJYed aj eYfGg GdeJYGQa (B...s
(3BNQgG (B:s
... (3hEf GbJVJ VeGfg bjeI GdOLGLI Ydi JbOjQ JdagG heYg jeJfY Cf jLH Ydjg (B... (3dcf gPG ajeG dh CQGO GdeGdc JZQjeg HbjeI GdOLGLI hCeG (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI(B4/499s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis